Draft proposal for a long-term EU-Africa Research and Innovation Flagship Programme on Food Nutrition Security and Sustainable agriculture (FNSSA) - (:unkn) unknown (My University, 2022)
The ERA-NET Cofund LEAP-Agri was launched following the recommendation of the European Union – African Union (AU-EU) High Level Policy Dialogue on STI (HLPD) and its first priority “Food and nutrition security and sustainable agriculture” (FNSSA). The first aim of LEAP-Agri was to fund Research and Innovation projects (R&I) between European and African research institutions. In this frame, 27 research and innovation (R&I) projects were funded with participants from the two continents. LEAP-Agri demonstrated that it is possible to involve, with the support of a top up funded by EU, 24 funding bodies from 18 EU and AU countries, all of them committing national budget. The second main aim of LEAP-Agri was to propose a flagship programme in the light of this cofunded call experience.The LEAP-Agri partners propose that this flagship programme should target agroecology topics addressing sustainable agricultural practices, farm development, management of soil erosion and of water access, promotion of species of interest in changing climate conditions, access to seeds and supporting farmers. The projects should participate to producing knowledge and recommendation to face the common AU-EU challenges of scaling farms for economic viability in order to ensure well-being of animals, farmers and consumers, nutrition and food security, limit greenhouse gas emission and global warming, promote biodiversity and protect soils and natural resources. It has to be written and aligned with the current national and intercontinental AU-EU research strategic agendas, in particular the current R&I FNSSA Roadmap approved by both Unions, and build on the results already obtained in the national and bi-continental R&I programmes for FNSSA. At this turning point for the FNSSA in terms of environmental and societal challenges, no R&I programme can be successful if no attention is paid to the involvement of a wide range of relevant stak
Keywords: African Research